Peer bank behavior, economic policy uncertainty, and leverage decision of financial institutions - Lee, Chien-Chiang; Lee, Chi-Chuan; Zeng, Jhih-Hong; Hsu, Yu-Ling (Journal of Financial Stability, 2017)
This paper explores the determinants for the leverage decision of financial institutions via the channels of bank-specific characteristics, peer bank behavior, and economic policy uncertainties, which are critical to appropriately control the risk of the financial system and explain the cross-sectional heterogeneity in risk-taking behavior among financial institutions. Our results indicate that bank-specific characteristics are the most influential one among the three channels for leverage decision of financial institutions, while the other two channels also exhibit significant effects on the leverage decision. We further note that economic policy uncertainty may affect their leverage decisions through the channels of their shifting lending behavior and risk-taking capacity.